Description of Eutetrapha weni n. sp. from Guizhou, China (Coleoptera: Cerambycidae: Lamiinae: Saperdini) - Huang, Gui-Qiang; Lin, Mei-Ying (Zootaxa, 2016)
Eutetrapha weni n. sp. is described from Leigongshan, Guizhou, China.